The Possibility of COVID-19 Pandemic in Eliminating Burning Activities: A Case Study at Ogan Komering Ilir Regency, South Sumatera - Lailan Syaufina; Muhammad Hudzaifah Rihuljihad; Ati Dwi Nurhayati (Jurnal Manajemen Hutan Tropika, 2021)
Forest and land fires occur almost every year in South Sumatera Province, including at Ogan Komering Ilir (OKI) Regency, mainly due to uncontrolled burning activities. This region has the largest peatland responsible for the adverse haze impacts. The advent of the coronavirus (COVID-19) pandemic in early 2020 has triggered massive consequences across the global communities, including Indonesia. Therefore, large-scale regulations on social restrictions were enacted. The purpose of this study is to analyze the variations in hotspots as forest and land fire indicators before and during the COVID-19 pandemic in OKI as well as to determine the rainfall effects. Daily Terra/Aqua MODIS satellite feeds and rainfall data between January 2018 and December 2020 served as the research materials. Subsequently, the paired t-test and correlation assessment were used to examine the hotspot variations in both datasets, respectively. The results showed significant statistical differences before and during the pandemic. Consequently, social restrictions were assumed to instigate the decline in burning activities. Furthermore, the rainfall demonstrated a vulnerable correlation to the hotspots, indicating that human factor was more pronounced as a fire trigger.